Chaperonin GroEL/GroES Over-Expression Promotes Aminoglycoside Resistance and Reduces Drug Susceptibilities in Escherichia coli Following Exposure to Sublethal Aminoglycoside Doses - Goltermann, Lise; Sarusie, Menachem V.; Bentin, Thomas (Frontiers in Microbiology, 2016)
Antibiotic resistance is an increasing challenge to modern healthcare. Aminoglycoside antibiotics cause translation corruption and protein misfolding and aggregation in Escherichia coli. We previously showed that chaperonin GroEL/GroES depletion and over-expression sensitize and promote short-term tolerance, respectively, to this drug class. Here, we show that chaperonin GroEL/GroES over-expression accelerates acquisition of streptomycin resistance and reduces susceptibility to several other antibiotics following sub-lethal streptomycin antibiotic exposure. Chaperonin buffering could provide a novel mechanism for emergence of antibiotic resistance.